IMPROVING PLANT EFFICIENCY OF BADAK LNG BY FINDING THE BEST IMPROVEMENT PROGRAMS - Rais Bahtiar, Muhamad
As an energy company, PT Badak NGL continues to innovate to improve the energy efficiency in their plant operation. However, as the amount of feed gas continues to decline, the percentage of fuel gas increases gradually. The reduced amount of feed gas results in a low load factor of the operating equipment, causing inefficient plant operation. The 2018 benchmark results show that PT Badak NGL’s energy efficiency performance is below average. The energy efficiency of plant operation is one of the Key Performance Indicators (KPI) which formulated in terms of Plant Thermal Efficiency (PTE), Feed Gas to LNG Ratio, and Steam to LNG Ratio. Although the KPI targets related to energy efficiency are almost always achieved, there is a trend of decreasing target every year. Using the Focus Group Discussion (FGD) method, energy reviews were conducted to determine each plant area's Significant Energy Use (SEU). Furthermore, the root cause analysis can be made in a Current Reality Tree (CRT). The Value-Focused Thinking (VFT) method is used in formulating alternative solutions for each cause of energy inefficiency. Analytic Hierarchy Process (AHP) is used as a decision-making tool from the alternative solutions. Sensitivity analysis is also carried out to ensure the robustness of the decisions made. Ten controllable root causes have been solved by developing internal procedures or studies, while eight outstanding causes can be solved with five alternative solutions. AHP, which was carried out using the criteria of cost, impact on energy efficiency, completion time, and complexity showed that there are top three priority solutions that must be implemented as soon as possible, namely the building energy management project, the LED replacement project, and flow and pressure indicators installation for pumps. The proposed strategy is set with a completion target of three years.